Commander–community ties after civil war. (July 2021) - Martin, Philip A
Ex-rebel military commanders play a central role in peacebuilding after civil war. Yet the influence and mobilization power of these actors is not uniform: in some areas commanders retain strong ties to civilian populations after war's end, while in other areas such ties wither away. This article analyses a novel dataset of former rebel-occupied localities in Côte d'Ivoire to investigate why commander–community linkages endure or decline after post-conflict transitions. The findings support a theory of political accountability: commanders retained political capital and access to networks of supporters in areas where insurgents provided essential goods to civilians during war. By contrast, where insurgents' wartime rule involved abuse and coercion, commanders were less likely to sustain strong ties. These findings challenge the conventional wisdom that violent warlordism explains the persistence of rebel commanders' power in peacetime. Rather, effective wartime governance may create regionally embedded strongmen who can in turn disrupt postwar state-building.